Adsorption of hidrogen peroxide on the surface of silica – titania mixed oxide obtained by the sol-gel processing method - Gonçalves, José Eduardo; Rodrigues Filho, Ubirajara Pereira; Franco, Douglas Wagner; Gushikem, Yoshitaka (Eclética Química, 2007)
This work describes the sol-gel mixed oxide SiO 2 /TiO 2 property, ST, as prepared, and submitted to heat treatment a 773 K, STC. SEM and EDS images show, within magnification used, a uniform distribution of the TiO 2 particles in SiO 2 /TiO 2 matrix. Both, ST and STC adsorb hydrogen peroxide on the surface and through EPR and UV-Vis diffuse reflectance spectra, it was possible to conclude that the species on the surface is the peroxide molecule attached to the Lewis acid site of titanium particle surface, α Ti(H 2 O 2 ) + . As the material is very porous, presumably the hydrogen peroxide molecule is confined in the matrix pores on the surface, a reason why the adsorbed species presents an exceptional long lived stability.